GUIDELINES FOR THE USE OF MEDIATION TO RESOLVE DISPUTES IN SOLVING THE PROBLEM OF THE OMBUDSMAN'S STUDY - Suttikanung, Sanchai (Rangsit Journal of Law and Society, 2025)
This study report the objective is to study the dispute mediation process for use in solving complaints from the Ombudsman, which consists of procedures and methods for mediating disputes and using the results of mediation in resolving complaints from the Ombudsman. Comparative study of important agencies before filing a lawsuit and after filing a lawsuit with the court. in order to get the appropriate guidelines for using the dispute mediation process to resolve complaints from the Ombudsman. Studies have shown that mediation is a popular dispute resolution option. Widely used nowadays, whether it be mediation of disputes before and after filing a lawsuit, both civil cases, criminal cases, and administrative cases. Government agencies have introduced mediation in disputes by law. Steps and procedures clearly defined There is also a central law, the Dispute Mediation Act 2019, that government agencies use as criteria for mediating disputes. For the Ombudsman, the main role and duty is to receive complaints. Consider and resolve complaints, and there were a number of complaints. It is quite necessary to use the method of mediation to solve the complaint. However, since the Ombudsman has not yet issued regulations and laid down criteria and guidelines for dealing with this matter, therefore The researcher therefore studied related laws and regulations. Including procedures and formats for mediating disputes. that government agencies have adopted and implemented, which turned out to be appropriate in solving the problem Complaints from the Ombudsman, and it is appropriate to issue regulations and lay down rules and guidelines regarding Mediation of disputes is clear and concrete and can be used to resolve complaints through mediation according to the specified criteria. This makes the Ombudsman's resolution of complaints faster and more efficient. It promotes reconciliation between government agencies and government officials and complainants and sustainable benefits.